Pemetaan Publikasi Literasi Media di Scopus Tahun 2019-2023 - Khairunnisa, Farah Nabila; Rizal, Edwin; Winoto, Yunus (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
The urgency of media education skills in the modern era has made media literacy research increasingly diverse. However, this diversity needs to be matched with adequate information regarding publication mapping. Therefore, this research aims to analyze trends in media literacy research to identify the direction of trends and future research opportunities using bibliometric analysis and a quantitative approach. The population includes 1,786 scientific publications on media literacy from 2019 to 2023 after filtering based on document type and keywords, resulting in a sample of 1,046 articles. The research findings indicate a positive trend, with an increase in publication frequency each year from 2019 to 2023. Through VOSViewer analysis, 51 keywords appeared in at least ten documents, then grouped into seven clusters. In general, media literacy research each year focuses on discussing misinformation and disinformation issues. In addition, the analysis also revealed the presence of rarely discussed keywords, such as